PATHWAY ANALYSIS USING A HYBRID OF SVM & SCAD - Muhammad Faiz Misman, 1985-, author; Mohd. Saberi Mohamad, author; Safa'ai Deris, 1955-, author; Siti Zaiton Mohd. Hashim, author (Johor Bahru, Johor : Penerbit UTM Press, 2017)
Includes bibliographical references and index